Two-Way Symmetrical Communication Model dalam Strategi Public Relations Berbasis Kecerdasan Buatan (AI) - Amalia, Izza; Muhamad Khadafi Firman; Amalia Tresna Fadhilah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The development of artificial intelligence (AI) brings fundamental transformation to contemporary public relations (PR) practice. This article examines the relevance and application of the Two-Way Symmetrical Communication model developed by Grunig and Hunt (1984) in AI-based PR strategies. Using a critical literature study approach and conceptual analysis, this study argues that AI is not merely an automation tool, but an enabler that strengthens the principles of symmetrical-dialogic communication between organizations and their publics. AI integration, which encompassing NLP-based sentiment analysis, responsive chatbots, predictive analytics, and real-time monitoring systems, enables organizations to listen, respond, and adapt to public needs more accurately and quickly. However, AI application in PR also raises serious ethical challenges, particularly regarding data privacy, algorithmic bias, and the risk of communication depersonalization. This study proposes an AI-Augmented Two-Way Symmetrical PR (AI-TWS-PR) framework that integrates technological capabilities with human-centered communication ethics principles. Conceptual findings indicate that AI-mediated symmetrical approaches have the potential to enhance stakeholder relationship management effectiveness while simultaneously strengthening organizational legitimacy and public trust.